Mitochondria dysfunction in Charcot Marie Tooth 2B Peripheral Sensory Neuropathy - Yingli Gu; Flora Guerra; Mingzheng Hu; Alexander Pope; Kijung Sung; Wanlin Yang; Simone Jetha; Thomas A. Shoff; Tessanya Gunatilake; Owen Dahlkamp; Linda Zhixia Shi; Fiore Manganelli; et al. (Communications Biology, 2022)
The Rab7V162M mutation associated with Charcot Marie Tooth 2B peripheral neuropathy causes mitochondrial fragmentation in patient-derived fibroblasts and primary cultured dorsal root ganglion sensory neurons from E18 mouse embryos.